Promoting well-being through group drumming with mental health service users and their carers. Issue 1 (1st January 2018) - Ascenso, Sara; Perkins, Rosie; Atkins, Louise; Fancourt, Daisy; Williamon, Aaron
ABSTRACT: Purpose : Music has been linked with well-being across clinical and community settings. Yet, research has focused on assessment of single dimensions of well-being and on the typical receiver of support services. Acknowledging the burden that a caring role encompasses and integrating recent proposals for a multifaceted definition of well-being, we explore the extent to which group drumming interventions translate into multidimensional well-being change for both mental health service users and carers. Method : Thirty-nine participants engaged in one of a series of community drumming programmes were assessed via semi-structured interviews (n = 11) and focus groups (n = 28) at the end of each programme. Data were analysed using IPA. Results and Conclusion : Emotional, psychological and social dimensions of well-being emerged for both patients and carers, accounted for through six themes: (1) hedonia: positive affect and pleasant physical effects of drumming; (2) agency: initiative and sense of control; (3) accomplishment: non-specific and in relation to musical goals; (4) engagement, through focus and flow; (5) a redefinition of self, through self-awareness, construction of a positive identity, self-prospection and incorporation of a musical identity; and (6) social well-being, through connectedness and positive relationships. The potential of such interventions for clinical contexts is discussed.